Lipid and fatty acid biomarkers as proxies for environmental contamination in caged mussels Mytilus galloprovincialis. (October 2015) - Signa, Geraldina; Di Leonardo, Rossella; Vaccaro, Antonino; Tramati, Cecilia Doriana; Mazzola, Antonio; Vizzini, Salvatrice
Highlights: Mussels transplanted in a highly polluted site showed contaminant bioaccumulation. Lipid class change over time indicated a biochemical stress response to pollution. Fatty acids indicated lipid peroxidation followed by compensatory/adaptive processes. Fatty acids suggested infections of bacteria or symbiosis with detoxifying ones. Lipids and fatty acids turned out robust proxies of contamination-induced stress. Abstract: Mussels ( Mytilus galloprovincialis ) were transplanted from a reference site (Syracuse harbour) to an impacted site (Augusta Bay) from January to July 2013 to assess the biochemical response of caged mussels to high trace element and polycyclic aromatic hydrocarbon (PAH) contamination, using lipid and fatty acid (FA) biomarkers. Sediment and mussels were analysed to assess contaminant bioavailability in the study sites and bioaccumulation in mussel tissue. Trace elements (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, V, Zn) and PAHs were significantly higher in mussels from Augusta than in those from Syracuse, mirroring the different environmental contamination. The biological impact quotient (BIQs), which indicates the potential biological impact of mussel-accumulated contaminants, reflected the highest contaminant concentrations found in Augusta and their temporal trend, which increased from the start of the experiment to 3–4 months after transplanting, followed by a decrease, as indication of mussel detoxification processes. Lower condition index (CI) and phospholipids (PL), as well as higher total (TL) and neutral lipids (NL) in mussels from Augusta, indicated the occurrence of a physiological and biochemical stress response to pollutant exposure and accumulation. Differences in FA composition, especially polyunsaturated (PUFA), essential (EFA) and non-methylene interrupted dienoic (NMID) FAs between the study sites revealed the occurrence of stress-induced lipid peroxidation, followed by compensatory/adaptive processes in Augusta mussels. The marked increase in bacterial biomarkers, mainly cyclopropyl (CY) FAs, reflecting the greater bioaccumulation of chemicals in the Augusta mussels, may be the result of bacterial infections or symbiosis with bacteria involved in detoxification processes.